Exploring the Clinical Relevance of p31comet in Head and Neck Squamous Cell Carcinoma through UALCAN database analysis - Henriques, Ana C. Henriques; Silva , João P. N.; Pinto, Bárbara; Silva, Patricia M. A.; Bousbaa, Hassan (Scientific Letters, 2024)
The p31comet protein plays a pivotal role in regulating spindle assembly checkpoint silencing and is overexpressed in several cancers, including oral cancer. Despite this, its exact roles in tumorigenesis and its prognostic significance remain unclear. In this study, using the UALCAN cancer database, we analyzed p31comet expression and its correlation with clinical indicators in Head and Neck Squamous Cell Carcinoma (HNSCC). Our findings revealed a significant upregulation of p31comet in HNSCC patients. Interestingly, we observed a positive correlation between p31comet expression and known interactors such as MAD2L1 and TRIP13, as well as regulators of p31comet expression. Furthermore, we found that p31comet expression was notably increased in tumor samples exhibiting alterations in the mTOR pathway and the SWI/SNF chromatin remodeling complexes. Intriguingly, HNSCC patients with high p31comet expression showed a tendency towards better prognosis compared to those with low/medium expression levels. This tendency did not reach statistical significance, likely due to variations in patient cohort sizes within the database. In summary, our findings suggest that increased p31comet expression could be a potential marker for tumor occurrence and metastasis in HNSCC patients, opening avenues for further research to understand its prognostic significance.